Reconstructing Ḥadīth Discourse in the Digital Age: From Text to Discourse - Salman, Abdul Matin bin (Journal of Ecohumanism, 2024)
This article explores the transformation of the Prophet’s ḥadīth from a fundamental religious text into a living discourse within culture and the practices of Muslims in the digital era. Technology and digital media have reshaped the understanding, dissemination, and integration of prophetic values into daily life. Using hermeneutic approaches, critical discourse analysis, and historical-comparative linguistics, this article examines how new methodologies in the social sciences and humanities provide deeper insights into these changes. Additionally, the article highlights the importance of considering both historical and contemporary shifts in the understanding of ḥadīth, including the impact of modernity and globalization. The analysis considers the role of scholars, institutions, and digital platforms in shaping new interpretations and applications of ḥadīth. The findings suggest that while traditional understandings of ḥadīth remain influential, there is an increasing openness to diverse interpretations that address contemporary issues and challenges faced by Muslim communities worldwide. The results indicate not only a growing openness to diverse interpretations but also reveal specific ways in which modernity and globalization have redefined traditional ḥadīth scholarship, influencing both the content and context of these interpretations.